Nephroprotective Effects of Sunkist Peel Ethanol Extract on Diabetic Nephropathy - Mutia, Maya Sari; Ginting, Chrismis Novalinda; Yulizal, OK; Suhartomi, Suhartomi; Sihotang, Widya Yanti (Faculty of Medicine, Universitas Padjadjaran, 2024)
The most common long-term diabetic complication is diabetic nephropathy which, in most cases, falls into the End-Stage Kidney Disease. Numerous studies on the nephroprotective effects of citrus fruit have been conducted recently. This study was performed to investigate the phytochemical properties of Sunkist peel ethanol extract and their possible effects on improving diabetic nephropathy. To get the extract, the Sunkist peels were macerated and the extract was analyzed by GC-MS. An in vivo assay of five different groups of 25 male Wistar rats was then performed using the extracts. The groups included control, standard, 500 mg/kg extract, 750 mg/kg extract, and 1,500 mg/kg BW extract. All rats were sacrificed after 28 days of treatment and VEGF level serum and kidney histology analysis were performed. The VEGF data were first analyzed descriptively, followed by one-way ANOVA or Kruskal-Wallis test based on the data distribution. Meanwhile, the kidney histology was observed and narratively described. Results showed that the Sunkist peel ethanol extract has a potential effect to suppress the VEGF level (p-value < 0.05). The extract at the highest dose revealed the mildest pathology damage in the form of tubular structure degeneration without any glomerular damage. This study indicates that Sunkist peel extract has nephroprotective effects from its various phytochemical compounds that work as antioxidants and anti-inflammation.